Powering The World With Hydrogen - Theresia Asteria (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
The global energy consumption has been on the rise worldwide as developing nations begin to industrialize and as consumers in developed nations buy more energy consuming appliances to make life more comfort- able. If the current trends continue, we may face an energy shortage in future. The phrase "hydrogen economy" refers to programs at using hydrogen as an energy carrier to replace hydrocarbon fuels and reduce emissions pro- duced by their consumption. Technologies such as fuel cells developed for cars, buses, power generation and other applications, along with the infra- structural implications of their broad and increasing use, are being de- monstrated in many countries around the world. Activities related to the hydrogen economy are covered on a country by country basis, where applicable.